UPAYA PENINGKATAN PENGETAHUAN MELALUI PENYULUHAN KESIAPAN DALAM MENGHADAPI MENARCHE DINI PADA ANAK DI SD MIN 1 BANTA-BANTAENG KOTA MAKASSAR - Nurafriani, Nurafriani; Sastika Sumi, Susi; Irmayani, Irmayani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
Adolescence is a period of transition from children to adulthood, during which many physical and psychological developments occur. One of the physical developments that occur in children towards adolescence is menarche. Menarche is a condition in which a girl experiences her first menstruation or first menstrual bleeding through the birth canal as a sign of fertility. Menarche is a sign of sexual maturity in girls. Currently, children tend to experience menarche more quickly with an age range of 10-12 years. If this condition is not in line with the increase in children's knowledge about menarche, it will certainly cause feelings of anxiety, embarrassment, and not ready for the changes that are taking place. The purpose of doing this community service is to increase knowledge in children through counseling activities about readiness in dealing with early menarche. The results obtained are an increase in children's knowledge about readiness in facing menarche. The conclusion is that there is an effect of counseling on readiness in facing menarche on increasing knowledge in children